Notes to Philosophy 167: Class 1 -- Overview of the Course;Ptolemaic Astronomy -- Part 11. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Ptolemy's Almagest: Ptolemy's Model of Planetary Motion -- The Achievement of Ptolemaic Astronomy.; Generally corresponds to the video segment: Class 1, Part 11.